Comparison of minimally invasive surgical approaches for hysterectomy at a community hospital: robotic-assisted laparoscopic hysterectomy, laparoscopic-assisted vaginal hysterectomy and laparoscopic supracervical hysterectomy - Giep, Bang N. (Springer-Verlag, 2010)
The study reported here compares outcomes of three approaches to minimally invasive hysterectomy for benign indications, namely, robotic-assisted laparoscopic (RALH), laparoscopic-assisted vaginal (LAVH) and laparoscopic supracervical (LSH) hysterectomy. The total patient cohort comprised the first 237 patients undergoing robotic surgeries at our hospital between August 2007 and June 2009; the last 100 patients undergoing LAVH by the same surgeons between July 2006 and February 2008 and 165 patients undergoing LAVHs performed by nine surgeons between January 2008 and June 2009; 87 patients undergoing LSH by the same nine surgeons between January 2008 and June 2009. Among the RALH patients were cases of greater complexity: (1) higher prevalence of prior abdominopelvic surgery than that found among LAVH patients; (2) an increased number of procedures for endometriosis and pelvic reconstruction. Uterine weights also were greater in RALH patients [207.4 vs. 149.6 (LAVH; P < 0.001) and 141.1 g (LSH; P = 0.005)]. Despite case complexity, operative time was significantly lower in RALH than in LAVH (89.9 vs. 124.8 min, P < 0.001) and similar to that in LSH (89.6 min). Estimated blood loss was greater in LAVH (167.9 ml) than in RALH (59.0 ml, P < 0.001) or LSH (65.7 ml, P < 0.001). Length of hospital stay was shorter for RALH than for LAVH or LSH. Conversion and complication rates were low and similar across procedures. Multivariable regression indicated that LAVH, obesity, uterine weight ≥250 g and older age predicted significantly longer operative time. The learning curve for RALH demonstrated improved operative time over the case series. Our findings show the benefits of RALH over LAVH. Outcomes in RALH can be as good as or better than those in LSH, suggesting the latter should be the choice primarily for women desiring cervix-sparing surgery.